English Material with Intercultural Values for Tourism Students of Tertiary Level in Bali - Ni Putu Dian Utami Dewi; Ni Luh Puji Wiliani; Ketut Suka Raditya Jaya (LUNAR, 2026)
In recent years, Balinese government focus on developing cultural tourism as a strategic sector for regional growth. Tourism industry has a close relationship with the tourism institution that provide the industry with the ready-made workers. Existing materials have not adequately addressed the dual imperative of enhancing English proficiency while simultaneously fostering intercultural values. However, the scarcity of contextually relevant English learning materials for students in Cultural and Religious Tourism Study Programs remains a critical concern. This study adopts a qualitative case study design to investigate these issues. Data were collected through in-depth interviews, classroom observations, and document analysis involving 20 students from two Cultural and Religious Tourism Study Programs in Buleleng and Bangli Regencies, as well as four English lecturers. Drawing on the CIPP (Context, Input, Process, Product) evaluation model, the findings indicate several significant gaps. At the contextual level, the existing syllabus lacks systematic integration of domain-specific vocabulary and terminology related to tourism, culture, and religion. At the input level, instructional materials are insufficiently aligned with intercultural competencies and do not adequately support higher levels of language proficiency. From the process perspective, current teaching practices require substantial enhancement through the incorporation of innovative, authentic, and technology-integrated learning activities that meaningfully embed intercultural values. At the product level, assessment practices remain limited and should be diversified to better align with learning objectives and competency-based outcomes. Overall, this study highlights the pressing need for the development of integrated English learning materials that are context-sensitive, interculturally oriented, and pedagogically robust to support the demands of cultural tourism education in Bali.